Innovation in Cultivation of Caulerpa racemosa Based on Used Bottles: The Effect of Diversity of Seed Weight in Gerupuk Waters - Hawari, Muhammad Naufal; Cokrowati, Nunik; Syukur, Abdul (Jurnal Biologi Tropis, 2026)
Caulerpa racemosa is a type of seaweed that is often caught in nature. The importance of cultivating Caulerpa racemosa seaweed is to reduce dependence on natural fishing, thus reducing the Caulerpa racemosa ecosystem. The study aims to analyze the growth of Caulerpa racemosa seaweed using used bottles with different seed weights. The study was conducted in April 2026 using a completely randomized design (CRD) experimental method, consisting of three seed weight treatments, namely P1 (25 g), P2 (50 g), and P3 (75 g) with three replications. Maintenance for 14 days, the parameters observed included Growth, SGR, SR, Nitrate content, Phosphate, Antioxidants, Chlorophyll-a, and Water Quality. The results showed that the best growth occurred on the 7th day, with the P3 treatment reaching a weight of 100 g. The highest SGR value was obtained by the P1 treatment at 7.99%, while the highest SR value was in P1 at 181.3%. However, on the 14th day, all treatments experienced a decrease in growth, suspected to be influenced by changes in environmental conditions. The results of the Normality Test showed that the results were not normally distributed because P3 <0.05. Meanwhile, the results of the Homogeneity Test obtained homogeneous data because the significance value was >0.05. Continued ANOVA Test obtained results that did not have a significant effect, so it was not tested further with the Duncan test. Although growth decreased in the second week, water quality during the study was still within the range that supports the cultivation of C. racemosa. These findings indicate that the use of used plastic bottles has the potential to be an inexpensive, environmentally friendly cultivation medium and supports the development of sustainable seaweed cultivation.